DNA aptamers selected against potato spindle tuber viroid bind the viroid and differentially modulate infection - Takashi Naoi; Maria S. Kaponi; Rino Hashimoto; Shoya Kitabayashi; Akiko Kashiwagi; Teruo Sano (Plant Cell Reports, 2026)

Development of a pressure-induced triploidy protocol and its effects on growth performance and fertility in tambaqui Colossoma macropomum (Cuvier, 1816) - Aldessandro da C. Amaral; Lucas S. Torati; Luciana N. Ganeco-Kirschnik; Luciana C.V. Villela; André Silverio Pereira; Julia T. Lopes; Yury O. Chaves; Diogo T. Hashimoto; Velmurugu Puvanendran; Fernanda L. Almeida O'Sullivan (Aquaculture, 2026)

Veining style and size-scaling behavior throughout the generation and exhumation of subduction mélange: Evidence from Japan and Alaska - J.N. Hooker; S. Luciano; D.M. Fisher; A.J. Smye; Y. Hashimoto; T. Hosokawa; S.J. Elliott (Journal of Structural Geology, 2026)

Speciation of cesium in a radiocesium-bearing microparticle emitted from Unit 1 during the Fukushima nuclear accident by XANES spectroscopy using transition edge sensor - Yoshio Takahashi; Hikaru Miura; Shinya Yamada; Oki Sekizawa; Kiyofumi Nitta; Tadashi Hashimoto; Takumi Yomogida; Akiko Yamaguchi; Shinji Okada; Takaaki Itai; Hiroki Suga; Teruhiko Kashiwabara; et al. (Journal of Hazardous Materials, 2025)

Genetic selection for resistance to Francisella orientalis shows significant selection response in Nile tilapia - Baltasar F. Garcia; Jairo A. Restrepo-Arango; Marcelo S. Silva Filho; Elielma L. Sousa; John F.G. Agudelo; Vito A. Mastrochirico-Filho; Shisley C.S. Manso; Carolina S. Pereira; Danielle C. Dias; Antonio F.G. Leonardo; Fernando S. Fonseca; Leonardo Tachibana; et al. (Aquaculture, 2025)

A molecular assessment of species diversity in Tympanopleura and Ageneiosus catfishes (Auchenipteridae: Siluriformes) - Shizuka Hashimoto; Lúcia H. Rapp Py‐Daniel; Jacqueline S. Batista (Journal of Fish Biology, 2020)
In order to test the congruence of genetic data to the morphologically defined Neotropical catfish genera Tympanopleura and Ageneiosus and explore species diversity, we generated 17 DNA barcodes from five of six species of Tympanopleura and 12 of 13 species of Ageneiosus . To discriminate limits between species, an automatic barcode gap discovery (ABGD), a generalised mixed yule‐coalescent model (GYMC) and fixed distance thresholds Kimura two‐parameter (K2P; 3%) were used to discriminate putative species limits from the DNA barcodes. The ABGD, GMYC and K2P methods agreed by each generating 13 clusters: six in Tympanopleura (five nominal plus one undescribed species) and seven in Ageneiosus . These clusters corresponded broadly to the described species, except in the case of the Ageneiosus ucayalensis group ( A. akamai , A. dentatus , A. intrusus , A. ucayalensis , A. uranophthalmus and A. vittatus ). Haplotype sharing and low divergences may have prevented molecular methods from distinguishing these species. We hypothesise that this is the result of a recent radiation of a sympatric species group distributed throughout the Amazon Basin. One putative new species of Tympanopleura was also supported by the molecular data. These results taken together highlight the utility of molecular methods such as DNA barcoding in understanding patterns of diversification across large geographic areas and in recognising overlooked diversity.

Mitochondrial orf463 causing male sterility in radish is possessed by cultivars belonging to the ‘Niger’ group - H. Yamagishi; Y. Tanaka; S. Shiiba; A. Hashimoto; A. Fukunaga; T. Terachi (Euphytica, 2019)

High‐resolution mapping of daily climate variables by aggregating multiple spatial data sets with the random forest algorithm over the conterminous United States - Hirofumi Hashimoto; Weile Wang; Forrest S. Melton; Adam L. Moreno; Sangram Ganguly; Andrew R. Michaelis; Ramakrishna R. Nemani (International Journal of Climatology, 2019)
High‐resolution gridded climate data products are crucial to research and practical applications in climatology, hydrology, ecology, agriculture, and public health. Previous works to produce multiple data sets were limited by the availability of input data as well as computational techniques. With advances in machine learning and the availability of several daily satellite data sets providing unprecedented information at 1 km or higher spatial resolutions, it is now possible to improve upon earlier data sets in terms of representing spatial variability. We developed the NEX (NASA Earth Exchange) Gridded Daily Meteorology (NEX‐GDM) model, which can estimate the spatial pattern of regional surface climate variables by aggregating several dozen two‐dimensional data sets and ground weather station data. NEX‐GDM does not require physical assumptions and can easily extend spatially and temporally. NEX‐GDM employs the random forest algorithm for estimation, which allows us to find the best estimate from the spatially continuous data sets. We used the NEX‐GDM model to produce historical 1‐km daily spatial data for the conterminous United States from 1979 to 2017, including precipitation, minimum temperature, maximum temperature, dew point temperature, wind speed, and solar radiation. In this study, NEX‐GDM ingested a total of 30 spatial variables from 13 different data sets, including satellite, reanalysis, radar, and topography data. Generally, the spatial patterns of precipitation and temperature produced were similar to previous data sets with the exception of mountain regions in the western United States. The analyses for each spatially continuous data set show that satellite and reanalysis led to better estimates and that the incorporation of satellite data allowed NEX‐GDM to capture the spatial patterns associated with urban heat island effects. The NEX‐GDM data is available to the community through the NEX data portal.

A Cell Assay for Detecting Anti-PEG Immune Response against PEG-Modified Therapeutics - Taro Shimizu; Amr S. Abu Lila; Mizuki Awata; Yukiyo Kubo; Yu Mima; Yosuke Hashimoto; Hidenori Ando; Keiichiro Okuhira; Yu Ishima; Tatsuhiro Ishida (Pharmaceutical Research, 2018)

Clinical significance of Aspergillus species isolated from respiratory specimens in patients with Mycobacterium avium complex lung disease - K. Furuuchi; A. Ito; T. Hashimoto; S. Kumagai; T. Ishida (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Lead line in rodents: an old sign of lead intoxication turned into a new method for environmental surveillance - Fellipe Augusto Tocchini de Figueiredo; Junia Ramos; Erika R. Hashimoto Kawakita; Alina S. Bilal; Frederico B. de Sousa; William D. Swaim; Joao P. Mardegan Issa; Raquel F. Gerlach (Environmental Science and Pollution Research, 2016)

Relationships between capture-site characteristics and capture levels of the invasive mongoose on Amami-Oshima Island, Japan - H. Komine; K. Takeshita; S. Abe; T. Ishikawa; M. Kimura; T. Hashimoto; K. Kitaura; T. Morosawa; K. Seki; K. Kaji (Biological Invasions, 2016)

Impact of bacterial coinfection on clinical outcomes in pneumococcal pneumonia - S. Kumagai; T. Ishida; H. Tachibana; Y. Ito; A. Ito; T. Hashimoto (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Reductions in synaptic proteins and selective alteration of prepulse inhibition in male C57BL/6 mice after postnatal administration of a VIP receptor (VIPR2) agonist - Yukio Ago; Michael C. Condro; Yossan-Var Tan; Cristina A. Ghiani; Christopher S. Colwell; Jesse D. Cushman; Michael S. Fanselow; Hitoshi Hashimoto; James A. Waschek (Psychopharmacology, 2015)

Analysis of acquired resistance to metronomic oral topotecan chemotherapy plus pazopanib after prolonged preclinical potent responsiveness in advanced ovarian cancer - William Cruz-Muñoz; Teresa Di Desidero; Shan Man; Ping Xu; Maria Luz Jaramillo; Kae Hashimoto; Catherine Collins; Myriam Banville; Maureen D. O’Connor-McCourt; Robert S. Kerbel (Angiogenesis, 2014)

Human proximity and habitat fragmentation are key drivers of the rangewide bonobo distribution - Jena R. Hickey; Janet Nackoney; Nathan P. Nibbelink; Stephen Blake; Aime Bonyenge; Sally Coxe; Jef Dupain; Maurice Emetshu; Takeshi Furuichi; Falk Grossmann; Patrick Guislain; John Hart; et al. (Biodiversity and Conservation, 2013)

Translation termination factor eRF3 is targeted for caspase-mediated proteolytic cleavage and degradation during DNA damage-induced apoptosis - Yoshifumi Hashimoto; Nao Hosoda; Pinaki Datta; Emad S. Alnemri; Shin-ichi Hoshino (Apoptosis, 2012)

Characteristics and osteogenic differentiation of stem/progenitor cells in the human dental follicle analyzed by gene expression profiling - H. Aonuma; N. Ogura; K. Takahashi; Y. Fujimoto; S. Iwai; H. Hashimoto; K. Ito; Y. Kamino; T. Kondoh (Cell and Tissue Research, 2012)

Effects of renal function on the pharmacokinetics and pharmacodynamics of prophylactic cefazolin in cardiothoracic surgery - T. Kosaka; K. Hosokawa; N. Shime; F. Taniguchi; T. Kokufu; S. Hashimoto; H. Fujiwara; H. Yaku; N. Sugioka; K. Okada; N. Fujita (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Removal of Cr(VI) from aqueous solutions by the culm of bamboo grass treated with concentrated sulfuric acid - M. Koroki; S. Saito; H. Hashimoto; T. Yamada; Masakazu Aoyama (Environmental Chemistry Letters, 2010)

Proliferation of kuchijirosho causative agent in a fugu‐derived cell line - E Hashimoto; T Miyadai; M Ohtani; S‐I Kitamura; M‐J Oh (Journal of Fish Diseases, 2008)
Kuchijirosho is a fatal disease of commercially cultured fugu, Takifugu rubripes . The transmissible nature of kuchijirosho strongly suggests that an infectious pathogen is the causative agent. Because it is filtrable, the agent is thought to be a virus; however, it has not yet been identified. The lack of a permissive cell line for the putative kuchijirosho‐causing agent (KCA) has hindered research on the identification of this pathogen. We inoculated brain extract prepared from kuchijirosho‐affected fugu onto an established fugu cell line, fugu eye, and observed that cytopathic effect appeared 7 days after inoculation. Injection of the culture medium of infected fugu eye cells into fugu resulted in the onset of kuchijirosho, indicating that fugu eye cells are able to proliferate KCA. An infectious fraction separated by sodium iottalamate density gradient centrifugation showed a density of 1.15 g mL −1 equivalent to that of KCA derived from affected fugu brain. To determine whether the genome of KCA is RNA or DNA based, nucleotide synthesis inhibitors were applied to inoculated fugu eye cell line to influence the production of KCA. 5‐Fluorouracil but not IUdR showed a concentration‐dependent inhibition of KCA yield. These results suggest that KCA is an RNA virus.

Nucleotide sequence analysis of seven Japanese isolates of Plantago asiatica mosaic virus (PlAMV): a unique potexvirus with significantly high genomic and biological variability within the species - K. Komatsu; Y. Yamaji; J. Ozeki; M. Hashimoto; S. Kagiwada; S. Takahashi; S. Namba (Archives of Virology, 2008)

Complete nucleotide sequence of asparagus virus 3 - M. Hashimoto; J. Ozeki; K. Komatsu; H. Senshu; S. Kagiwada; T. Mori; Y. Yamaji; S. Namba (Archives of Virology, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Genome sequence of a Japanese isolate of Radish mosaic virus: the first complete nucleotide sequence of a crucifer-infecting comovirus - K. Komatsu; M. Hashimoto; K. Maejima; J. Ozeki; S. Kagiwada; S. Takahashi; Y. Yamaji; S. Namba (Archives of Virology, 2007)

Clathrin is involved in organization of mitotic spindle and phragmoplast as well as in endocytosis in tobacco cell cultures - H. Tahara; E. Yokota; H. Igarashi; H. Orii; M. Yao; S. Sonobe; T. Hashimoto; P. J. Hussey; T. Shimmen (Protoplasma, 2007)

Hypoxia-induced hyaluronan synthesis by articular chondrocytes: the role of nitric oxide - K. Hashimoto; K. Fukuda; K. Yamazaki; N. Yamamoto; T. Matsushita; S. Hayakawa; H. Munakata; C. Hamanishi (Inflammation Research, 2006)

Noggin and basic FGF were implicated in forebrain fate and caudal fate, respectively, of the neural tube-like structures emerging in mouse ES cell culture - Shunmei Chiba; Manae S. Kurokawa; Hideshi Yoshikawa; Ritsuko Ikeda; Mitsuhiro Takeno; Mamoru Tadokoro; Hiroaki Sekino; Takuo Hashimoto; Noboru Suzuki (Experimental Brain Research, 2005)

Involvement of Aquaporin-5 Water Channel in Osmoregulation in Parotid Secretory Granules - M. Matsuki; S. Hashimoto; M. Shimono; M. Murakami; J. Fujita-Yoshigaki; S. Furuyama; H. Sugiya (The Journal of Membrane Biology, 2005)

Horizontal and Vertical Distribution of Estrogenic Activities in Sediments and Waters from Tokyo Bay, Japan - S. Hashimoto; A. Horiuchi; T. Yoshimoto; M. Nakao; H. Omura; Y. Kato; H. Tanaka; K. Kannan; J. P. Giesy (Archives of Environmental Contamination and Toxicology, 2005)

Genetic diversity and phylogeny of Japanese sake-brewing rice as revealed by AFLP and nuclear and chloroplast SSR markers - Z. Hashimoto; N. Mori; M. Kawamura; T. Ishii; S. Yoshida; M. Ikegami; S. Takumi; C. Nakamura (Theoretical and Applied Genetics, 2004)

Current Levels of Dioxins in Surface Soils from Santiago, Chile - Y. Takazawa; R. Verdugo; P. Richter; K. Kitamura; J.-W. Choi; S. Hashimoto; H. Ito; Y. Shibata; M. Morita (Bulletin of Environmental Contamination and Toxicology, 2004)

High frequency Agrobacterium-mediated transformation and plant regeneration via direct shoot formation from leaf explants in Beta vulgaris and Beta maritima - H. Hisano; Y. Kimoto; H. Hayakawa; J. Takeichi; T. Domae; R. Hashimoto; J. Abe; S. Asano; A. Kanazawa; Y. Shimamoto (Plant Cell Reports, 2004)

Comparative Analysis of the Ribosomal Componentsof the Hydrogenosome-Containing Protist, Trichomonas vaginalis - Nobuko Arisue; Yasushi Maki; Hideji Yoshida; Akira Wada; LidyaB. Snchez; Mikls Mller; Tetsuo Hashimoto (Journal of Molecular Evolution, 2004)

Sleeping mound construction using coral fragments by the rockmover wrasse - S. Takayanagi; Y. Sakai; H. Hashimoto; K. Gushima (Journal of Fish Biology, 2003)
The rockmover wrasse Novaculichthys taeniourus was observed using coral fragments for mound construction on the reefs of Kuchierabu‐jima Island, Japan. The wrasse heaped between four and 71 pieces of coral fragments on each sand mound, and dived into the mound just before sunset. Coral fragments may facilitate the retention of sleeping sites under competition with other sand‐diving wrasses.

Effect of p-Nonylphenol on sperm motility in Japanese medaka (Oryzias latipes) - R. Kawana; C.A. Strüssmann; S. Hashimoto (Fish Physiology and Biochemistry, 2003)

Peripheral nerve regeneration through alginate gel: analysis of early outgrowth and late increase in diameter of regenerating axons - T. Hashimoto; Y. Suzuki; M. Kitada; K. Kataoka; S. Wu; K. Suzuki; K. Endo; Y. Nishimura; C. Ide (Experimental Brain Research, 2002)

Molecular taxonomy of vestimentiferans of the western Pacific and their phylogenetic relationship to species of the eastern Pacific - Kojima S.; Ohta S.; Yamamoto T.; Miura T.; Fujiwara Y.; Fujikura K.; Hashimoto J. (Marine Biology, 2002)

Construction of a high-resolution linkage map of a rice brown planthopper (Nilaparvata lugens Stål) resistance gene bph2 - H. Murai; Z. Hashimoto; P. N. Sharma; T. Shimizu; K. Murata; S. Takumi; N. Mori; S. Kawasaki; C. Nakamura (Theoretical and Applied Genetics, 2001)

Molecular taxonomy of vestimentiferans of the western Pacific and their phylogenetic relationship to species of the eastern Pacific. I. Family Lamellibrachiidae - Kojima S.; Ohta S.; Yamamoto T.; Miura T.; Fujiwara Y.; Hashimoto J. (Marine Biology, 2001)

A method for detecting myocardial abnormality by using a total current-vector calculated from ST-segment deviation of a magnetocardiogram signal - A. Kandori; H. Kanzaki; K. Miyatake; S. Hashimoto; S. Itoh; N. Tanaka; T. Miyashita; K. Tsukada (Medical & Biological Engineering & Computing, 2001)

A method for detecting myocardial abnormality by using a current-ratio map calculated from an exercise-induced magnetocardiogram - A. Kandori; H. Kanzaki; K. Miyatake; S. Hashimoto; S. Itoh; N. Tanaka; T. Miyashita; K. Tsukada (Medical & Biological Engineering & Computing, 2001)

Antibacterial characteristics of magnesium oxide powder - J. Sawai; H. Kojima; H. Igarashi; A. Hashimoto; S. Shoji; T. Sawaki; A. Hakoda; E. Kawada; T. Kokugan; M. Shimizu (World Journal of Microbiology and Biotechnology, 2000)

A major metabolite of aceclofenac, 4′-hydroxy aceclofenac, suppresses the production of interstitial pro-collagenase/proMMP-1 and pro-stromelysin-1/proMMP-3 by human rheumatoid synovial cells - R. Yamazaki; S. Kawai; Y. Mizushima; T. Matsuzaki; S. Hashimoto; T. Yokokura; A. Ito (Inflammation Research, 2000)

Temporal profile of visual evoked responses to pattern-reversal stimulation analyzed with a whole-head magnetometer - Tadashi Hashimoto; S. Kashii; Masashi Kikuchi; Yoshihito Honda; Takashi Nagamine; Hiroshi Shibasaki (Experimental Brain Research, 1999)

Interaction of citrus juices with pranidipine, a new 1,4-dihydropyridine calcium antagonist, in healthy subjects - K. Hashimoto; T. Shirafuji; H. Sekino; O. Matsuoka; H. Sekino; O. Onnagawa; T. Okamoto; S. Kudo; J. Azuma (European Journal of Clinical Pharmacology, 1998)

Anti-inflammatory effect of YPE-01, a novel diarylheptanoid derivative, on dermal inflammation in mice - R. Yamazaki; R. Aiyama; T. Matsuzaki; S. Hashimoto; T. Yokokura (Inflammation Research, 1998)

Molecular phylogeny of vestimentiferans collected around Japan, revealed by the nucleotide sequences of mitochondrial DNA - S. Kojima; R. Segawa; J. Hashimoto; S. Ohta (Marine Biology, 1997)

Production and recovery of an enzyme fromPseudomonas vesicularis var.povalolyticus PH that degrades polyvinyl alcohol - Y. Kawagoshi; Y. Mitihiro; M. Fujita; S. Hashimoto (World Journal of Microbiology and Biotechnology, 1997)

Modes of Seoul virus infections: persistency in newborn rats and transiency in adult rats - H. Kariwa; M. Kimura; S. Yoshizumi; J. Arikawa; K. Yoshimatsu; I. Takashima; N. Hashimoto (Archives of Virology, 1996)

Lactoferrin-mediated protection of the host from murine cytomegalovirus infection by a T-cell-dependent augmentation of natural killer cell activity - K. Shimizu; H. Matsuzawa; K. Okada; S. Tazume; S. Dosako; Y. Kawasaki; K. Hashimoto; Y. Koga (Archives of Virology, 1996)

Heat shock induces HIV-1 replication in chronically infected promyelocyte cell line OM10.1 - K. Hashimoto; M. Baba; K. Gohnai; M. Sato; S. Shigeta (Archives of Virology, 1996)

Identification of mutation sites of a temperature-sensitive mutant of HCMV DNA polymerase activity - S. Ihara; M. Takekoshi; N. Mori; S. Sakuma; J. Hashimoto; Y. Watanabe (Archives of Virology, 1994)

Unusual splice sites in the E1A?E1B cotranscripts synthesized in adenovirus type 40-infected A549 cells - S. Ishida; Y. Fujinaga; K. Fujinaga; N. Sakamoto; S. Hashimoto (Archives of Virology, 1994)

Antibody-dependent enhancement of hantavirus infection in macrophage cell lines - J. -S. Yao; H. Kariwa; I. Takashima; K. Yoshimatsu; J. Arikawa; N. Hashimoto (Archives of Virology, 1992)

Protective role of antigenic sites on the envelope protein of Hantaan virus defined by monoclonal antibodies - J. Arikawa; J. -S. Yao; K. Yoshimatsu; I. Takashima; N. Hashimoto (Archives of Virology, 1992)

Evidence for the presence of a genome-linked protein in infectious flacherie virus - Y. Hashimoto; A. Watanabe; S. Kawase (Archives of Virology, 1986)

Genetic and phenotypic characteristics of enterovirus 71 isolates from patients with encephalitis and with hand, foot and mouth disease - A. Hagiwara; T. Yoneyama; S. Takami; I. Hashimoto (Archives of Virology, 1984)

Enhanced production of interferon by ultraviolet irradiation and pretreatment with interferon in human diploid cells stimulated with polyinosinate-polycytidilate - H. Komatsu; N. Maehara; K. Shimoda; H. Hashimoto; T. Mori; T. Lee; S. Makino; M. Matumoto (Archives of Virology, 1982)